Vedolizumab plus basiliximab as second-line therapy for steroid-refractory lower gastrointestinal acute graft-versus-host disease - Gao, Zicheng; Fan, Zhiping; Liu, Zhi; Ye, Xu; Zeng, Yunxin; Xuan, Li; Huang, Fen; Lin, Ren; Sun, Jing; Liu, Qifa; Xu, Na (Frontiers in Immunology, 2024)
Background: Steroid-resistant (SR) lower gastrointestinal (LGI) tract graft-versus-host disease (GVHD) is the predominant cause of morbidity and mortality from GVHD after allogeneic stem cell transplantation (allo-HSCT). The role of vedolizumab for the treatment of SR-LGI-aGVHD remains uncertain. We aimed to assess the efficacy and safety of vedolizumab combined with basiliximab as second-line therapy for SR-LGI-aGVHD.To explore the efficacy of vedolizumab combined with basiliximab for SR-LGI-aGVHD. The primary endpoint was the overall response (OR) at day 28. Secondary and safety endpoints included durable OR at day 56, overall survival (OS), chronic GVHD (cGVHD), non-relapse mortality (NRM), failure-free survival (FFS) and adverse events.Results: Twenty-eight patients with SR-LGI-aGVHD were included. Median time to start of combination therapy after SR-LGI-aGVHD diagnosis was 7 (range, 4-16) days. The overall response rate (ORR) at 28 days was 75.0% (95%CI: 54.8%-88.6%), and 18 achieved a CR (64.3%, 95%CI: 44.1-80.7%). The durable OR at day 56 was 64.3% (95%CI: 44.1-80.7%). The 100-day, 6-month and 12 months OS rates for entire cohort of patients were 60.7% (95%CI:45.1%-81.8%) and 60.7% (95%CI:45.1%-81.8%), 47.6% (95%CI:31.4%-72.1%), respectively. The median failure-free survival was 276 days. (95% CI:50-not evaluable) 12 months NRM was 42.9% (95% CI: 24.1%-60.3%). The 1-year cumulative incidence of cGVHD was 35.7%. Within 180 days after study treatments, the most common grade 3 and 4 adverse events were infections. Nine (32.1%) patients developed Cytomegalovirus (CMV)reactivation complicated with bacterial infections (25.0%, CMV infection, 7.1%; CMV viremia). Epstein-Barr virus (EBV) reactivation was occurred in 5 patients (17.9%,95% CI:6.8%-37.6%). Only 3 patients (10.7%, 95% CI: 2.8%-29.4%) in our study developed pseudomembranous colitis.Conclusions: Vedolizumab plus basiliximab demonstrated efficacy of severe SR-LGI-aGVHD and were well-tolerated. Vedolizumab plus basiliximab may be considered as a potential treatment option for patients with LGI aGVHD.